Impact of Antioxidant and Anti-Inflammatory Functions of HDL in Diseases—2nd Edition - Carlo Cervellati; Judit Marsillach (Antioxidants)
In recent decades, significant advancements in lipidology have profoundly reshaped our understanding of the biological roles of lipids and lipoproteins, particularly high-density lipoproteins (HDLs) [...]